The Practical Use of Awareness Theory - Barney G. Glaser; Anselm L. Strauss (Grounded Theory Review: An International Journal, 2015)
In this chapter we shall discuss how our substantive sociological theory has been developed in order to facilitate applying it in daily situations of terminal care by sociologists, by doctors and nurses, and by family members and dying patients. The application of substantive sociological theory to practice requires developing a theory with (at least) four highly interrelated properties. (As we have demonstrated in this book and will discuss explicitly in the next chapter, a theory with these properties is also very likely to contribute to formal—i.e., general—sociological theory.)